The Importance of Radiological Patterns and Small Airway Disease in Long-Term Follow-Up of Postacute COVID-19: A Preliminary Study - Roberto Mogami; Ronaldo Carvalho Araújo Filho; Carolina Gianella Cobo Chantong; Fernando Carlos Santos de Almeida; Ana Célia Baptista Koifman; Gustavo Federico Jauregui; Thiago Thomaz Mafort; Hanna da Silva Bessa da Costa; Glenda Aparecida Peres dos Santos; Bruna Zangerolame de Carvalho; Gabriel da Silva Passos; Erick de Souza Barbosa; et al. (Radiology Research and Practice)
Postacute COVID-19 has become a relevant public health problem, and radiological and pulmonary function tests are tools that help physicians in decision-making. The objectives of this study are to characterize the findings and patterns on a chest radiograph (CXR) and computed tomography (CT) that are most important in the postacute phase and to evaluate how these changes correlate with clinical data, spirometry, and impulse oscillometry (IOS). This was a retrospective study of 29 patients who underwent CXR, CT, spirometry, and IOS. The inclusion criteria were age >18 years and persistent respiratory symptoms after four weeks. The exclusion criteria were radiological exams with low technical quality and non-COVID-19 acute lung diseases. The inferential analysis was carried out with the chi-square (χ2) or Fisher’s exact test to evaluate the interrelationships between the clinical and COVID-19 variables according to spirometry, IOS, CT, and CXR. In our sample, 19 patients were women (65.5%). The predominance of abnormal spirometry was associated with CT’s moderate/severe degree of involvement (p = 0.017; 69.2%, CI 95%: 44.1%–94.3%). There was no significant association between IOS and tomographic and radiographic parameters. A significant association was found between the classifications of the moderate/severe and normal/mild patterns on CT and CXRs (p = 0.003; 93.3%, CI 95%: 77.8%–100%). Patients with moderate/severe impairment on CXR were associated with a higher frequency of hospitalization (p = 0.033; 77.8%, CI 95%: 58.6%–97.0%) and had significantly more moderate/severe classifications in the acute phase than the subgroup with normal/mild impairment on CXR (p = 0.017; 88.9%, CI 95%: 74.4%–100%). In conclusion, the results of this study show that CXR is a relevant examination and may be used to detect nonspecific alterations during the follow-up of post-COVID-19 patients. Small airway disease is an important finding in postacute COVID-19 syndrome, and we postulate a connection between this pattern and the persistently low-level inflammatory state of the lung.